AUDIT OPERASIONAL TERHADAP PELAYANAN JASA DAN FASILITAS YANG DIBERIKAN OLEH PT. KAPUAS PALACE PONTIANAK KEPADA CUSTOMER - Wahyu B51109067, Gusti Fajar (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
This study was conducted with descriptive methods. Descriptive method as activities that include data collection in order to test or answer questions concerning the state of the running time of a basic research with the object of research at PT Kapuas Palace Pontianak. The data was collected by way of documentary studies, interviews, observations, and questionnaires. The purpose of this study is to find out information relating to operational procedures and factors that influence inefficiency operational procedures at PT. Kapuas Palace Pontianak. Analysis tools in use that standard operational procedures, risk control matrix, flowchart analysis and compliance test. The results showed that the procedure to service at PT Kapuas Palace Pontianak is executed in accordance with the provisions established, so it is considered to be good. However, there is still a lack of supervision and control by the management that affect operational inefficiencies such as lack of determination of risk and lack of communication between the part and the boss. The facilities provided by the hotel to the guest is good, but still there are some facilities that must be addressed in order to expedite the company's operations. Suggestions can I give you is the hotel management are expected to conduct supervision and control over the operations so as to create better results. The existence of strict sanctions for officers involved in the operations of the company. Doing improvements to the facilities of the hotel guests were still lacking as well as possible management or leadership to approach employees in its operations in order to create effective communication. Keywords: Operational Audit